Penerapan tasawuf pada pelaku ekonomi di lingkungan sekitar - Qomariyah, Rif'atul (Maliki Interdisciplinary Journal, 2025)
Sufism is an effort carried out by individuals with the aim of purifying their souls by moving away from the impact of a happy life on the world by getting closer to the Creator so that His presence in life. Sufism is also a branch of knowledge that focuses on the mind rather than the material, the hereafter rather than the mortal, and the mind rather than the born. The purpose of Sufism is to foster ethical aspects which include realizing the stability of the soul and the control of lust, as a system of introduction and approach to Allah in a mystical philosophical manner about the line of relationship between humans and God. What is done by the fried rice seller as an Islamic economic actor is ethics in doing business such as patience, honesty, trust and not harming others. Sincerity and tawakal, these Islamic economic actors have patience in running their business not only to get profits but to worship Allah. In practice, these Islamic economic actors implement the teachings of Sufism well in order to achieve an economic activity in accordance with the teachings of Sharia.Sufism as a madzhab institutionalism in Islam that focuses on moral development, teaches about human consciousness in material properties to spiritual natures.